Cartografia ambiental de Barão de Cotegipe, RS: subsídios para o planejamento municipal - Rovani, Franciele Francisca Marmentini (2013)
The study and the analysis about the relations between the social and environmental can be better understood and visualized throughout environmental maps that can sensitize the society to the reality. Through this context, this research has as the objective to analyze the geographic space of Barão de Cotegipe city, in the state of Rio Grande do Sul, with the emphasis on the natural and social constituent parts, represented by the Environmental Cartography and to identify the different units in the landscape. A special database was created in an environment of Geographic Information System with the use of SPRING Software in the version 5.0.6. The map of natural vulnerability, to the lack of the soil, was elaborated based on the information relating to the geomorphology, geology, soil, vegetation, and the use and occupation of the soil and the social potential map, resulted from an integration of natural, human, productive and institutional potential with the help of the language and programing of algebra processing. Afterwards, the information was organized and integrated in the synthesis map, the unit map of landscape, representative of reality in study. As a result, the maps of natural vulnerability to the soil lack that represented steady units, with the predominance of formation processes of soil and units moderated vulnerable, predominated the erosive processes were highlighter. The map of social potential represented equilibrium between dynamism and restriction, that is, units with a high potentiality were not identified neither in a low potentiality. In the unit map of landscape predominate the productive units in expansion (59.08%), allowing the expansion of the productive potential of sustainable and dynamic ways and the critical units of conservation (40.21%) characterized by the elevated natural vulnerability and low potentiality. Already, the production units in consolidation, considered ideals, represented only 0.05% of the municipal area, while the critical units in recovery accounted 0.66%, due to the high potential and high social vulnerability natural. In the units, in which predominated the natural vulnerability, special attention with relation to the natural and the agent that influence it are suggested, aiming at good social practice associated to the environmental politics in the process of economic decision make to enable the valorization and environment protection. In the productive units, characterized specially by the potentiality, the development of actions looking towards mainly to the productive development is recommended, because the diversity of the productive sector is fundamental to the occurrence of the consolidation and expansion of units, ensuring equilibrium between the environmental and the man, based on the sustainable use of natural resources. As a result, guided by the Environmental Cartography, the units were represented cartographically allowing the understanding and the visualization of environmental interaction and of the social dynamic with the natural environmental.